« Farces et Moralités » d'Octave Mirbeau - Kaczmarek, Tomasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2005)
Octave Mirbeau was an anarchist and radical writer who is known today for his powerful indictments of French society. He wrote to revenge this society for his upbringing. That's why the article treats of the dramaturgy of the author of The Torture Garden set within the wide frames of expressionism. A key enabling to decode the unconventional writings of Mirbeau lies in the plane of subjectivity, and specially in the Farces and Moralities, considered as dark comedies, in grotesque style. The article corroborates the contention about the original character of Mirbeau's Farces affecting the expressionistic aesthetics.
Forces and Moralities by Octave Mirbeau